Groundwater trace element changes were probably induced by the ML3.3 earthquake in Chaoyang district, Beijing - Chen, Yuxuan; Liu, Jianbo (Frontiers in Earth Science, 2023)
Geochemical composition changes in groundwater related to earthquakes had been documented in the previous studies, and most such studies focused the changes in major ions, hydrogen and oxygen isotopes, geochemical gases. Changes in trace elements were suggested to be more sensitive to small earthquake than the commonly used chemical constitutents such as major ions, while they had received less attention. Beijing is located in the Zhangjiakou-Bohai seismic belt, and frequent occurrence of small earthquakes. In this paper, we weekly collected groundwater samples during August 2021 to August 2022 from a hot spring in Yanqing district of Beijing. Each water sample analyzed 41 trace chemical composition. During the sampling, an earthquake with a magnitude of ML3.3 occurred in Chaoyang district of Beijing on February 3th, 2022, so these trace elements changes were systematically monitored before and after the earthquake: Li, Sc, Ti, Pb elements had upward changes before the earthquake. Cu, Nb, Th, Zn, Tl, U elements had downward changes before the earthquake. Eu (rare earth elements) had upward changes after the earthquake. At the same time, the earthquake caused no significant changes in the groundwater level in seismic monitoring well near the Songshan spring. Such responses indicate that trace elements are likely to be more sensitive to crustal strain than groundwater level. We considered that the earthquake-induced rock cracks before or after earthquake caused enhancing water-rock interaction and led to migration of trace elements between water column and rocks, as the mechanism to explain the trace elemental changes. This study probably provides a comprehensive assessment of the sensitivity of trace element constituents to the earthquake. Furthermore, we suggest that more long-term continuous monitoring and research of trace elements in Beijing and Zhangjiakou-Bohai Fault Zone should be considered to explore the response mechanism of groundwater geochemistry to earthquakes in the future.